Infection Patterns of Helminth Parasites in Mackerel Tuna (Euthynnus affinis Cantor, 1849) from Banten Waters, Indonesia - Muhammad Raihan Pambudi; Sulistiono Sulistiono; Risa Tiuria; Sonja Kleinertz (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
The study of zoonotic parasites is of extreme importance, because they can cause diseases in humans and can negatively impact the marketability of fisheries products. The present study aims to determine the infection patterns of helminth parasites infecting mackerel tuna in Banten waters, as well as to clarify possible negative impacts to its fish host. Mackerel tunas were caught from March to July 2020 in Banten Bay and Sunda Strait and obtained from Karangantu fishing port and Muara Angke fishing port. For parasite identification, different staining methods were used (KOH, Semichon’s acetocarmine). Helminth parasites that has been found in this study belonged to the taxa of Monogenea (1), Digenea (1), Nematoda (2) and Acanthocephala (2). The helminth parasite species with the highest prevalence was Hexostoma euthynni (P: 16.7%) from Banten Bay and Neorhadinorhynchus sp. (P: 53.3%) from Sunda Strait followed by a possible zoonotic parasite Anisakis sp. with 46.7% prevalence. In this study four new locality records were established. Pathogenic impacts from the isolated parasites to the examined fish could be expected, especially for the revealed H. euthynni, which may decrease the fish’s ability to perform proper respiration, cause irritation to gills, and anemia. Preventive actions on anthropogenic activities will be required in order to keep the natural conditions in the areas of Banten Bay and Sunda Strait. Regular fish parasite monitorings will lead to the sustainable use of fisheries resources, assess possible fish health impacts, and zoogeographical distributions of zoonotic and pathogenic parasites.